Is there a role of viral infection in cystic fibrosis exacerbation in children? - Hamed, Dina H; Soliman, Mai Sherif; Emam, Ola Soliman; El-Attar, Mona Mohsen (The Turkish Journal of Pediatrics, 2022)
Background. Cystic fibrosis (CF) is a degenerative disease distinguished by progressive epithelial secretory gland dysfunction associated with recurrent respiratory tract infections. Despite that bacteria have previously been studied as the main cause of CF airway damage, a strong effect of respiratory viral infections is also now recognized. We aimed to detect the relationship between viral infection and exacerbation in children with cystic fibrosis. Methods. This is a cross sectional observational study recruiting 60 patients diagnosed as CF following in Cystic Fibrosis Clinic, Children`s Hospital, Cairo University, throughout a period of 7 months. Their age ranged from 6 months to 13 years. Patients had nasal swabs and sputum samples obtained when they developed respiratory exacerbations. Multiplex PCR (polymerase chain reaction) technique was used to detect respiratory viruses from nasal swabs. Results. We detected viruses in 48 patients during exacerbation (80%), the most common virus was rhinovirus in 43.4% of patients, followed by bocavirus in 20%, adenovirus in 13.3%, enterovirus in 10% and human metapneumovirus in 6.7%. Co-infection with double viruses was detected in 10 patients. Bacterial infection was present in 56.7% of patients; the most common organism was Pseudomonas in 20% of patients, followed by Staphylococcus aureus, methicillin resistant Staphylococcus aureus, Klebsiella and Haemophilus influenzae. CRP was positive in 53.3% of patients. There was a significant relationship between sputum positive bacterial culture and each of influenza A virus, enterovirus and human metapneumovirus. Conclusions. This study demonstrated that exacerbation in cystic fibrosis may be exaggerated by viral infections such as influenza A and enterovirus necessitating hospitalization which shows the important protective role of vaccination. Also, a strong relationship was detected between some viruses such as enterovirus, human metapneumovirus and influenza and between bacterial infection.
Keywords: cystic fibrosis; exacerbation; respiratory viruses; rhinovirus